A Violation of Woman’s Rights under Tradition of Belis in East Nusa Tenggara, Indonesia - Wawan Suriadi; Shahrul Mizan bin Ismail (Unram Law Review, 2021)
Indonesia as a legal state has ratified several instruments of international law in order to protect women’s rights. But restraint and violations of women’s rights are still common. In East Nusa Tenggara, high dowry or Belis often trigger violence against women. This is triggered by the perception that the transfer of women’s rights when the dowry or Belis has been paid by the men to the women’s family who ultimately give the ability and arbitrariness of men to commit acts of violence. So, the purpose of this study is to review more comprehensively how the practice of giving Belis or dowry in terms of international law and analyze the extent to which international and national law provides protection for the rights of women who are victims of violence. This research is legal doctrinal research using qualitative method. This research was conducted in literature by studying legislation at the national and international level, books, articles, journals, scientific reports related to the issues studied. From this study, it was found that the practice of giving Belis in the form of dowry in marriage is a cultural practice that is also protected by domestic and international law as part of the way of life or cultural rights. Acts of violence in the form of restraint on women’s rights due to the repayment of Belis is a violation of women’s human rights. So that these two things must be seen from two different sides. The number of national and international legal instruments does not guarantee that it can overcome the problem of violence against women. The legal culture of society in the form of high legal awareness and the willingness and commitment of the state is one step forward in order to provide protection of women’s rights.